Европий киришма атомлари киритилган кремнийга магнит майдон таъсири (SCIENCE and SOCIETY, 2023)
After diffusion of europium impurity atoms, its electric parameters were studied by the The Van der Pauw (VDP) method. The obtained scientific research results were examined in the surface morphology using an atomic force microscope (AFM). The lattice constant of the materials was calculated with the help of Bragg Brentano`s law using X-ray diffraction on the XRD pattern of the Si sample.